2014
DOI: 10.1002/aur.1380
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Sectional Evidence for a Decrease in Cognitive Function With Age in Children With Autism Spectrum Disorders?

Abstract: Autism spectrum disorders (ASD) are associated with early disturbances in brain maturation processes and these interferences presumably have their consequences for the progressive emergence of cognitive deficits later in life, as expressed in intelligence profiles. In this study, we addressed the impact of age on cognitive functioning of 6- to 15-year-old children and adolescents with ASD. Intelligence profiles were measured by the Wechsler Intelligence Scale for Children and compared among four consecutive ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Taken together, our findings from the comparison of LT and ASD toddlers and the longitudinal data for the ASD group at 30 and 44 months is consistent with previous research reporting significant comprehension-production discrepancy profiles in children with ASD (Barbaro and Dissanayake 2012; Barneveld et al 2014; Ellis Weismer et al 2010; Hudry et al 2010; Kover et al 2013; Luyster et al 2008; Maljaars et al 2012; Seol et al 2014; Volden et al 2011). However, we found a higher percentage of children with ASD who exhibited a discrepant comprehension-production profile in our smaller ASD-LT comparison sample (91%) than our broader longitudinal sample of children with ASD at a mean age of 30 months (62%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Taken together, our findings from the comparison of LT and ASD toddlers and the longitudinal data for the ASD group at 30 and 44 months is consistent with previous research reporting significant comprehension-production discrepancy profiles in children with ASD (Barbaro and Dissanayake 2012; Barneveld et al 2014; Ellis Weismer et al 2010; Hudry et al 2010; Kover et al 2013; Luyster et al 2008; Maljaars et al 2012; Seol et al 2014; Volden et al 2011). However, we found a higher percentage of children with ASD who exhibited a discrepant comprehension-production profile in our smaller ASD-LT comparison sample (91%) than our broader longitudinal sample of children with ASD at a mean age of 30 months (62%).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, our longitudinal findings confirm previous cross-sectional results (Seol et al 2014), indicating that the relative comprehension weakness diminishes from toddlerhood through the preschool period. Other cross-sectional studies examining older children, however, have reported discrepant comprehension-production profiles after age six (Barneveld et al 2014; Kover et al 2013). Future longitudinal studies need to tease apart whether the discrepant comprehension-production profile later in development re-emerges or whether those who persist in exhibiting a discrepant comprehension-production profile at 66 months continue to display this profile throughout development.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Being a neurodeveloppemental disorder, the impact of AS might be different throughout life, as shown by some cross sectional studies (e.g. Barneveld, Swaab, van Engeland, & de Sonneville, 2014). It is relevant to take age into account when evaluating intelligence in ASD individuals.…”
Section: Introductionmentioning
confidence: 99%